2021
DOI: 10.3389/fimmu.2021.671595
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast Heterogeneity: A Factor That Cannot Be Ignored in Immune Microenvironment Remodeling

Abstract: Cancer-associated fibroblasts (CAFs) are important, highly heterogeneous components of the tumor extracellular matrix that have different origins and express a diverse set of biomarkers. Different subtypes of CAFs participate in the immune regulation of the tumor microenvironment (TME). In addition to their role in supporting stromal cells, CAFs have multiple immunosuppressive functions, via membrane and secretory patterns, against anti-tumor immunity. The inhibition of CAFs function and anti-TME therapy targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 98 publications
2
45
0
1
Order By: Relevance
“…Targeted CAF therapy can potentially inhibit metastasis and cancer progression by reducing immunosuppression and remodeling the tumor microenvironment. Therapeutic targeting of FAP has been described in different modalities, such as vaccines, oncolytic viruses, and nanoparticles [26]. In preclinical studies, CAF-S1 FAP+ has shown to cause resistance to anti-PD-L1 immunotherapy and reduce antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted CAF therapy can potentially inhibit metastasis and cancer progression by reducing immunosuppression and remodeling the tumor microenvironment. Therapeutic targeting of FAP has been described in different modalities, such as vaccines, oncolytic viruses, and nanoparticles [26]. In preclinical studies, CAF-S1 FAP+ has shown to cause resistance to anti-PD-L1 immunotherapy and reduce antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, cancer-associated fibroblasts exerted a strong immunomodulatory regulation, mainly suppressing the immune system and promoting tumour progression. 51,52 Thus, we deduced that CNTN1 might take a negative regulation in the tumour immune microenvironment.…”
Section: F I G U R E 8 Correlation Analysis In Different Algorithms B...mentioning
confidence: 93%
“…This is a base for the formation of metastases and resistance to chemo/actinotherapy. CAF-derived exosome efficiency mainly depends on the specific miRNAs in their cargo [73,122,136,[148][149][150][151][152][153][154][155][156][157][158][159][160] (summarised in Table 4). Cancer wasting and cachexia are present in many patients in the terminal phase of malignant disease [161].…”
Section: Effect Of Cancer Cell-derived Exosomes (Caexos) On the Funct...mentioning
confidence: 99%